2019
DOI: 10.1016/j.heliyon.2019.e01197
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic, hypolipidemic and antioxidant effects of green sprouts juice and functional dairy micronutrients against streptozotocin-induced oxidative stress and diabetes in rats

Abstract: Hyperglycemia, the mark normal for diabetes and associated disorders are the main goals of natural diabetes therapies. In this context, the present research was designed to study the effects of fenugreek sprouts juice (FS), barley sprouts juice (BS), cell-free probiotic extract (cell-free PE), whey protein hydrolysate (WPH) and their mixture on diabetic rats. Free radical scavenging activity, total phenolic contents (TPC) and total flavonoid contents (TFC) of each item mentioned were determined. Diabetes was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Free radicals make a significant contribution to the development of DM as such, which causes damage to beta cells. 33 , 34 Treatment with AND may protect the cells from free radicals caused by STZ. Zhang reported that AND increases insulin and prevents the loss of beta cells and their dysfunction in soleus muscles.…”
Section: Resultsmentioning
confidence: 99%
“…Free radicals make a significant contribution to the development of DM as such, which causes damage to beta cells. 33 , 34 Treatment with AND may protect the cells from free radicals caused by STZ. Zhang reported that AND increases insulin and prevents the loss of beta cells and their dysfunction in soleus muscles.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated antioxidant activity of F5 and F9 may be due to the increase of banana and onion peels as well as lettuce and whey protein in the formulation especially that these ingredients have potent antioxidant activities as confirmed by Park et al (2018) and Mohamed et al (2019). Values are mean of three replicates ± SD, number in the same column followed by the same letter is not significantly different at 0.05 level; ND: Not detected Color is one of the most important quality features of vegetable and fruit products, where it is the first thing consumers see (Sudha et al, 2015).…”
Section: Physiochemical Characteristics Of Different Soup Mixturesmentioning
confidence: 91%
“…(Cao & Xiong, 2017). Oral administration of a mixture of different sprouts juices, probiotics, and WPH significantly reduced oxidative stress in rats (Mohamed et al., 2019).…”
Section: Discussionmentioning
confidence: 99%